1996
DOI: 10.1002/(sici)1099-1352(199634/12)9:5/6<509::aid-jmr293>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-shielded dye-affinity chromatography

Abstract: Polymer-shielded dye-affinity chromatography is a form of chromatography in which the dye matrix forms complexes with a nonionic, water-soluble polymer such as poly(vinylpyrrolidone) or poly(vinyl alcohol), prior to the column chromatography of a crude protein extract, the idea being that polymer shielding of the dye will prevent nonspecific interactions between the target protein and the dye. The concept of polymer shielding and a strategy for the rational selection of polymers suitable as shielding agents ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Chemistries for immobilization of dye ligands via epoxide-activated spacers instead of the conventional coupling to surface hydroxyls were recently investigated by Scoble and Scopes, 385 who showed that the epoxide immobilization route gave materials with considerably higher ligand density. Mattiasson et al 386 addressed the nonspecific interactions of dye affinity sorbents by shielding the ligands with layers of nonionic, water-soluble polymers such as poly(vinylpyrrolidone) or poly(vinyl alcohol). The same authors also reviewed new developments in dye affinity for bioprocessing, dealing specifically with new dyes and conditions for the protein -ligand attachment and detachment steps.…”
Section: Enzyme -Inhibitor Complexesmentioning
confidence: 99%
“…Chemistries for immobilization of dye ligands via epoxide-activated spacers instead of the conventional coupling to surface hydroxyls were recently investigated by Scoble and Scopes, 385 who showed that the epoxide immobilization route gave materials with considerably higher ligand density. Mattiasson et al 386 addressed the nonspecific interactions of dye affinity sorbents by shielding the ligands with layers of nonionic, water-soluble polymers such as poly(vinylpyrrolidone) or poly(vinyl alcohol). The same authors also reviewed new developments in dye affinity for bioprocessing, dealing specifically with new dyes and conditions for the protein -ligand attachment and detachment steps.…”
Section: Enzyme -Inhibitor Complexesmentioning
confidence: 99%
“…However, even with an ideal ligand density, it is still possible for weak specific interactions to occur between CB and contaminant proteins, which will potentially decrease the purity of the final product. In order to ameliorate this problem, Mattiasson et al [11] introduced the concept of 'polymer shielding', whereby one loads on to the affinity column a polymer that is less strongly bound than the product molecule but more strongly bound than contaminants, thereby 'shielding' the column from non-specific adsorbates. Here we assess the potential for an intrinsic shielding approach, whereby BSA, a protein known to show a weak interaction with CB, is co-immobilized to the support.…”
Section: Introductionmentioning
confidence: 99%